Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
[tex] |d| = \sqrt{ {( - 6 - ( - 3))}^{2} + {( - 4 - ( - 4))}^{2} } \\ = \sqrt{ {( - 3)}^{2} + {0}^{2} } = \sqrt{9} \\ |d| = 3[/tex]
[tex]\large{\rm{\underline{\underline{Answer:}}}}[/tex]
For two given points, (x1,y1) and (x2, y2) the distance between the points can be calculated by,
Distance formula,
d=√((x2 - x1)²+(y2 - y1)²
Given points,
(x1, y1) = (-4, -3)
(x2, y2) = (-4, -6)
Put the values,
d = √(-4 + 4)² + (-6 + 3)²
d = √ 0 + (-3)²
d = √9
d = [tex] \pm[/tex] 3
But distance is always positive. Hence, the distance between the pair of points. (-4,-3) and (-4,-6) is 3 units.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.